The Moderating Effect of the Status of Using a Product on the Relationship Between Brand Experience and Word of Mouth Recommendations - Ngatno, Ngatno; Apriatni, Endang P (Archives of Business Research, 2021)
The purpose of this study was to examine the moderating effect of the status of using the product on the relationship between brand experience, satisfaction, loyalty and brand recommendation. Structural equation modeling (SEM) with multi groups was used for data analysis. The results of this study indicate that there is a strong relationship between brand experience, satisfaction, loyalty and brand recommendation. The effect of brand experience and brand satisfaction on WOM recommendations was higher in the new user group than in the established user group. While the effect of brand loyalty on WOM recommendations was higher for established users than for new users. The effect of brand experience on brand satisfaction was greater for established users than for new users. While the effect of brand experience on brand loyalty was greater in the new-user group, it was not significant. Finally, the effect of brand satisfaction on brand loyalty was greater for established users than for new users.